Hubungan Pola Asuh Orang Tua dan Lingkungan Sekolah Terhadap Motivasi Belajar Siswa Kelas X SMA Negeri 1 Siak - Dini Febriyola; Dinda Zulva Janesya; Syahnur Rahman (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2022)
This research was carried out at SMA Negeri 1 Siak which aims to find out how the relationship between parenting patterns and the school environment is related to students' learning motivation. The research methods used in this research are qualitative research methods and comparative causal research or can also be called ex post facto research. In this study, the researchers used questionnaires to students to collect research data. The questionnaire distributed to students was a questionnaire on parenting and learning motivation. To determine whether or not there is an effect of parenting on students' motivation to learn, an analysis was performed using simple linear regression analysis technique. Before conducting data analysis, a prerequisite analysis test was conducted. Data analysis was carried out using a computer with the SPSS for Windows version 20 program. The population in this study were students of class X SMA N 1 Siak and the sample used was 87 students. Based on the ANOVA data, the calculated F test results were 0.812 with Sig. 0.097. Hypothesis decision making is based on the level of significance, if Sig. 0.05 then it is significant and if Sig. 0.05 then it is not significant. The results showed that Sig. = 0.097 0.05, thus it can be stated that the results are not significant.